An open-label, single-arm, phase 1 study to assess biomarker effects, efficacy and safety of ofatumumab in patients with refractory chronic lymphocytic leukemia. Issue 10 (3rd October 2015) - Patton, William Nigel; Lindeman, Robert; Butler, Andrew C.; Kipps, Thomas J.; Jewell, Roxanne C.; Laubscher, Kevin H.; Zhou, Yan Yan; Lewis, Eric; Sedoti, Donna; Witman, Philip; Fang, Lei; Chan, Geoffrey
Abstract : This open-label, phase 1 study evaluated the effects of ofatumumab on QTc intervals, safety, efficacy, B-cell and neutrophil counts, complement levels, and cytokine and chemokine concentrations. Fourteen patients with fludarabine-refractory chronic lymphocytic leukemia received 12 ofatumumab infusions. A higher maximum infusion rate of 400 mL/h was tested at the first two doses and was well tolerated. The 43% overall response rate was similar to previous data (42–51%). B-cell depletion was observed along with complement consumption; median C2 and CH50 levels appeared lower during monthly dosing in patients who responded. Responding patients appeared to have higher median levels of certain pro-inflammatory cytokines and lower median levels of certain immunotolerant cytokines than patients who did not respond. Ofatumumab-induced complement-dependent cytotoxicity activity can be detected clinically by measuring complement and may be associated with clinical activity. The potential relationship between changes in complement or cytokines and clinical response to ofatumumab warrants further study.